Pediatric neuroblastic tumors: A critical evaluation of cytomorphological features for risk stratification on aspiration cytology. Issue 5 (11th February 2020) - Behera, Gayatri; Chhabra, Gaurav; Mishra, Pritinanda; Sable, Mukund
Abstract: Background: Neuroblastic tumor (NT) is the most common extracranial solid tumor of childhood with variable outcome which again depends on risk stratification related to distinct biology of the tumor. The use of fine‐needle aspiration (FNA) material for evaluation of cytomorphological parameters and risk stratification in NTs using cytology prognostic score (PS) is limited in routine practice. Methods: We reviewed 38 FNA cytology cases diagnosed as pediatric small round cell tumor between time period June 2017 to December 2019 for clinical, cytomorphological and immunohistochemical features. Results: Ten out of 38 small round cell tumors were NTs. All 10 cases were further subclassified according to International Neuroblastoma Pathology Classification into undifferentiated neuroblastoma (n = 1), poorly differentiated neuroblastoma (n = 5), differentiating neuroblastoma (n = 2), and ganglioneuroblastoma (n = 2). Cytologic PS was done using the morphological criteria as described previously in literature. The patients were divided into favorable and unfavorable cytomorphological prognostic categories with a cut off scoring of 12. A score of more than 12 is associated with high risk morphology and advanced stage. All cases with PS > 12 (n‐4) (unfavorable cytomorphology) had a poor outcome compared to six patients with PS < 12 (n‐6) (favorable cytomorphology). Conclusion: Aspiration cytology can be used as a first line investigation to evaluate the cytomorphological features for risk stratification and diagnosis in patients with NTs using cytological prognostic scoring system. A larger multi‐centric validation study necessitates for cytological risk stratification.